2021
DOI: 10.4236/ojped.2021.114068
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, Clinical, Therapeutic and evolutionary Aspects of Children Living with HIV in Guédiawaye, Senegal

Abstract: Introduction: HIV infection in children is a major public health problem. The objective of this study carried out in the paediatric department of the Centre Hospitalier Roi Baudouin de Guédiawaye, was to evaluate the epidemiological, clinical, therapeutic and evolutionary aspects of a cohort of children with HIV over a 15-year period and to determine the factors associated with discontinuation of treatment and transition to second-line treatment. Patients and Methods: This was a descriptive and analytical cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 9 publications
1
3
1
Order By: Relevance
“…Almost half of the children were severely underweight (51.06%) and almost a quarter was moderately underweight (20.21%). These results differed from those of studies in Pikine-Dagoudane [20] and Guediawaye [14], where 11.8% and 5% of children were moderately chronically malnourished, 8.6% and 1% were severely chronically malnourished, 11.9% and 6% were moderately acutely malnourished, and 17.4% and 1% were severely wasted, respectively.…”
Section: Discussioncontrasting
confidence: 89%
See 4 more Smart Citations
“…Almost half of the children were severely underweight (51.06%) and almost a quarter was moderately underweight (20.21%). These results differed from those of studies in Pikine-Dagoudane [20] and Guediawaye [14], where 11.8% and 5% of children were moderately chronically malnourished, 8.6% and 1% were severely chronically malnourished, 11.9% and 6% were moderately acutely malnourished, and 17.4% and 1% were severely wasted, respectively.…”
Section: Discussioncontrasting
confidence: 89%
“…The prevalence of malnutrition was 62.77% for acute malnutrition, 41.49% for chronic malnutrition, and 71.27% for underweight. Our results are those obtained in a study carried out in Guediawaye, Senegal, in 2020, which showed a high prevalence of acute malnutrition (29.3%) compared with that of chronic malnutrition (20.4%) and underweight (25.5%) [14]. In terms of acute malnutrition, our results showed that 41.49% of the patients had severe acute malnutrition and 21.28% had moderate acute malnutrition.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations